The Association Between Embryo Quality, Number of Transferred Embryos and Live Birth Rate After Vitrified Cleavage-Stage Embryos and Blastocyst Transfer - Zhu, Qianqian; Lin, Jiaying; Gao, Haoyuan; Wang, Ningling; Wang, Bian; Wang, Yun; Kuang, Yanping (Frontiers in Physiology, 2020)
Objective The single-embryo transfer (SET) is the recommended approach to improve the live birth rate and reduce the complications related with multiple pregnancies. However, the physicians generally chose to transfer two embryos when the embryo quality decreased. The effect on the in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) outcomes following the transfer of a poor-quality embryo (PQE) along with a good-quality embryo (GQE) has been explored. However, previous studies were limited by the fresh embryo transfer cycles or the small sample size. Methods A retrospective cohort study was performed among 26,676 women (the mean age was 31.72 years) undergoing first frozen embryo transfer (FET) from January 2011 to December 2017. Patients were grouped into five subgroups, including SET with one GQE (SET-GQE, 2235 patients for cleavage-stage embryo transfer and 756 patients for blastocyst transfer), SET with one PQE (SET-PQE, 148 patients for cleavage-stage embryo transfer and 362 patients for blastocyst transfer), double-embryo transfer with two GQE (DET-2GQE, 20,461 patients for cleavage-stage embryo transfer and 519 patients for blastocyst transfer), double-embryo transfer (DET) with one GQE plus one PQE (DET-GQE+PQE, 1541 patients for cleavage-stage embryo transfer and 266 patients for blastocyst transfer), and DET with two PQE (DET-2PQE, 228 patients for cleavage-stage embryo transfer and 160 patients for blastocyst transfer). Multivariable logistic regression models were performed after controlling for other potential confounders to estimate the effect of number and quality of transferred embryos on pregnancy outcomes. Result Although the live birth rate was significantly higher after DET-GQE+PQE compared with SET-GQE for cleavage-stage embryo transfer [574 of 1541 (37.25%) vs. 571 of 2235 (25.55%)], no significant difference was found between DET-GQE+PQE and SET-GQE for blastocyst transfer [143 of 266 (53.76%) vs. 325 of 756 (42.99%)]. However, DET-GQE+PQE also had the highest multiple live births in both cleavage-stage embryo transfer [134 of 1541 (8.70%)] and blastocyst transfer [46 of 266 (17.29%)]. The live birth rate after SET-PQE significantly decreased in comparison with SET-GQE [cleavage-stage embryo transfer: 18 of 148 (12.16%) vs. 571 of 2235 (25.55%); blastocyst transfer: 107 of 362 (29.56%) vs. 325 of 756 (42.99%)] and significantly increased after DET-2GQE compared with SET-GQE [cleavage-stage embryo transfer: 9357 of 20,461 (45.73%) vs. 571 of 2235 (25.55%); blastocyst transfer: 313 of 519 (60.31%) vs. 325 of 756 (42.99%)]. The live birth rate was also not different between DET-2PQE and SET-GQE for cleavage-stage embryo transfer and blastocyst transfer [cleavage-stage embryo transfer: 75 of 228 (32.89%) vs. 571 of 2235 (25.55%); blastocyst transfer: 74 of 160 (46.25%) vs. 325 of 756 (42.99)]. Conclusion In order to minimize the risk of multiple births, the data from this study did not support transferring DET with a GQE plus a PQE compared with SET with a GQE, especially for blastocyst transfer. However, the proportion of patients older than 35 years was small (12.07% for patients aged 36–39 years and 7.31% for patients 40 years or older), which limited the generalization of these results to other population.